Airtime for Newcomers: Radio for Migrants in the United Kingdom and West Germany, 1960s–1980s. Issue 1 (2nd January 2020) - Hilgert, Christoph; Just, Alina L.; Khamkar, Gloria
Abstract : This article explores the British and West German public service radio's abilities to reflect on and to address the specific needs and expectations of migrant groups in their programmes between the 1960s and 1980s. Mechanisms of social inclusion and exclusion alike can be investigated here. Empirically, it is based on comparisons of radio broadcasts on and for different immigrant communities, produced by BBC Radio Leicester on/for the post-war Asian migrants in England and by West German public service broadcasting on/for 'Gastarbeiter' (foreign workers) as well as for 'Spätaussiedler' (German repatriates from East Europe). Radio is studied as an agent of identity management and citizenship education. Not only did radio talk about migrants and migration to introduce these topics and the newcomers to the local population. It also offered airtime to selected migrant communities to cater for their needs and interests as well as to facilitate their difficulties of adjusting to an unfamiliar environment.